2006
DOI: 10.1099/vir.0.81468-0
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of the VP2 gene of Chicken anemia virus affects virus replication, cytopathology and host-cell MHC class I expression

Abstract: Chicken anemia virus (CAV) is an immunosuppressive pathogen of chickens. To further examine the role of viral protein 2 (VP2), which possesses dual-specificity protein phosphatase (DSP) activity, in viral cytopathogenicity and its influence on viral growth and virulence, an infectious genomic clone of CAV was subjected to site-directed mutagenesis. Substitution mutations C87R, R101G, K102D and H103Y were introduced into the DSP catalytic motif and R129G, Q131P, R/K/K150/151/152G/A/A, D/E161/162G/G, L163P, D169… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…In contrast to the effect on CTL, natural killer (NK) cells were not affected by CIAV infection [81]. Based on their studies of CIAV infection in MSB-1 cells, Peters et al [82] suggested that VP2 may also play a role in immunosuppression through down-regulation of major histocompatibility complex (MHC) class I antigens. The importance of this observation for immunosuppression is difficult to evaluate because the assumption is that CIAV-infected cells will become apoptotic.…”
Section: Chicken Infectious Anemia Virusmentioning
confidence: 99%
“…In contrast to the effect on CTL, natural killer (NK) cells were not affected by CIAV infection [81]. Based on their studies of CIAV infection in MSB-1 cells, Peters et al [82] suggested that VP2 may also play a role in immunosuppression through down-regulation of major histocompatibility complex (MHC) class I antigens. The importance of this observation for immunosuppression is difficult to evaluate because the assumption is that CIAV-infected cells will become apoptotic.…”
Section: Chicken Infectious Anemia Virusmentioning
confidence: 99%
“…In contrast to the effect on CTL, natural killer (NK) cells were not affected by CIAV infection (Markowski-Grimsrud and . Based on the studies in MSB-1 cells, Peters et al (2006) recently suggested that VP2 may also play a role in immunosuppression through downregulation of major histocompatibility complex (MHC) class I antigens. The importance of this observation for immunosuppression is difficult to evaluate because the assumption is that CIAV-infected cells will become apoptotic.…”
Section: Chicken Infectious Anaemia Virusmentioning
confidence: 99%
“…The CAV genome is circular and ~2.4Kb in length, encoding three distinct viral proteins from a single transcribed mRNA containing 3 overlapping ORF's. VP3, renamed apoptin for its ability to promote apoptosis in transformed and tumorigenic cell lines, is the primary cause of the CAV's deleterious effects [98][99][100]. VP2, a dual-specificity protein phosphatase, is essential for efficient viral replication and has mild apoptotic effects [99].…”
Section: Chicken Anemia Virus (Cav) and Apoptinmentioning
confidence: 99%
“…Apoptin has been shown to induce apoptosis in a variety of tumorigenic cell lines, but normal cells are spared from death. In non-transformed cells, threonine 108 is not phosphorylated and apoptin segregates to the cytoplasm, preventing induction of apoptosis [100]. Tumorigenic or transformed cells, however, target apoptin to the nucleus [102], where it initiates an unknown series of events leading to apoptosis.…”
Section: Chicken Anemia Virus (Cav) and Apoptinmentioning
confidence: 99%